Atomic Layer Deposition of TiOx/Al2O3 Bilayer Structures for Resistive Switching Memory Applications1. Issue 7 (28th July 2014) - Zhang, Hehe; Aslam, Nabeel; Reiners, Marcel; Waser, Rainer; Hoffmann‐Eifert, Susanne
Abstract : The resistive switching (RS) properties of a thin Al2 O3 layer and TiO x /Al2 O3 bilayers integrated into TiN/metal oxide/Pt crossbar devices are investigated for future memristive device (ReRAM) applications. The oxide bilayer stack is realized in consecutive atomic layer deposition (ALD) processes at 300 °C without any post‐annealing step. Stoichiometric Al2 O3 and oxygen‐deficient TiO x thin films are grown from dimethylaluminum isopropoxide [DMAI: (CH3 )2 AlOCH(CH3 )2 ] and tetrakis‐dimethlyamido‐titanium [TDMAT: Ti(N(CH3 )2 )4 ], respectively, as the metal sources, and water as the oxygen source. High insulating characteristics are confirmed for as‐grown amorphous Al2 O3 films with a dielectric permittivity of 8.0 and disruptive field strength of about 7 MV cm −1, whereas the oxygen‐deficient TiO x shows semiconducting behavior. The bipolar‐type RS characteristics of TiN/TiO x /Al2 O3 /Pt cells show a strong dependence on both oxide layer thicknesses. A stable OFF/ON state resistance ratio of about 10 5 is obtained for the bilayer structure of 5 nm TiO x and 3.7 nm Al2 O3 . Abstract : The resistive switching of TiO x /Al2 O3 bilayers integrated in µ‐crossbar devices is investigated for future ReRAM. The bilayer stack is realized in consecutive atomic layer depositions (ALD) at 300 °C. Amorphous Al2 O3 films exhibit a dielectric permittivity of 8.0 and disruptive field strength of 7 MV cm −1, whereas the oxygen‐deficient TiO x is semiconducting. The bipolar‐type resistive switching characteristics of TiN/TiO x /Al2 O3 /Pt cells show a strong dependence on both oxide layer thicknesses.